Faktor Pendorong dan Penghambat Green Manufacturing pada Sektor Agroindustri - Viariani, Wahyu; Rizki, Atiyatur; Muflikh, Yanti Nureani (Universitas Galuh, 2024)
The rapid growth of the manufacturing industry has created a number of economic, environmental and social problems, including global warming and environmental pollution due to waste. This has resulted in increased awareness of environmental issues throughout the world which has encouraged the development of green manufacturing, including in the agro-industrial sector. However, there are still many industries, especially agro-industry, that are not yet aware of the importance of implementing green manufacturing. Therefore, this research aims to analyze the views of previous research on green manufacturing and analyze the driving and inhibiting factors for green manufacturing in agro-industry so that it can become evaluation material for various related parties in the future. The method used in this research is Systematic Literature Review (SLR) using 20 related articles. The results of this research show that green manufacturing is defined as a strategy where manufacturing companies prioritize creating products using minimal raw materials and high energy efficiency, replacing input materials with environmentally friendly ones, and reducing production waste with an effective recycling approach. The drivers for implementing green manufacturing in agro-industry are regulations or policies, knowledge and commitment. Meanwhile, obstacles to the implementation of green manufacturing in agro-industry are insufficient government support for industry, weak regulations for implementing green manufacturing, price competition, and difficulty in obtaining raw materials.